2020
DOI: 10.1590/s2175-97902020000118499
|View full text |Cite
|
Sign up to set email alerts
|

Lipid-rich fraction of the sclerotium of Tiger Milk Mushroom Lignosus rhinocerotis (Agaricomycetes) attenuates LPS-induced inflammation in BV2 cells via Nrf2 pathway

Abstract: Lignosus rhinocerotis (tiger milk mushroom) is widely used by the indigenous people of Malaysia as a traditional remedy. The present study was carried out in order to evaluate the antioxidant, cytotoxic and anti-neuroinflammatory activities of L. rhinocerotis extract on brain microglial cells (BV2). The antioxidant activity was evaluated by 2,2-diphenyl-1-picryhydrazyl (DPPH•), 2,2'-azinobis (3-ethylbenzthiazoline-6-sulphonic acid) (ABTS•+) scavenging assays, and ferric reducing antioxidant power (FRAP). The F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 32 publications
(35 reference statements)
1
12
0
Order By: Relevance
“…The biological structure of different culture media has an effect on the nutrients and bioactive components of the mushroom, and will therefore create different effects on the medicinal effects (show Table 1, 2 and 3). Considering all this, it supports the findings of the previously mentioned researchers [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30].…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The biological structure of different culture media has an effect on the nutrients and bioactive components of the mushroom, and will therefore create different effects on the medicinal effects (show Table 1, 2 and 3). Considering all this, it supports the findings of the previously mentioned researchers [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30].…”
Section: Resultssupporting
confidence: 88%
“…and Picoa spp.) had dose-dependent cytotoxic effects on H1299, HUVEC, PC3, SiHa, HeLa, EAC, HepG2, BV2, HEK-293, MCF7, A549, BGC-823, HGC-27, MDA-MB-231, MRC-5, RAW 267.4, Colo-205, LS-513, Du-145, HT29, HCT-116, HCT-116, Lu-04, Bre-04, L929 cell lines [20][21][22][23][24][25][26][27][28][29][30]. Our data (see Table 3) may differ from those reported by the other investigators mentioned above.…”
Section: Resultsmentioning
confidence: 99%
“…velutipes, Lactarius salmonicolor, Pleurotus ostreatus, Polyporus squamosus, and Russula anthracina ) in from Anatolia where all selected species were reported to have cis -linoleic acid contributing to the highest portion in the fatty acid composition, which varied from 22.39 % to 65.29 % [ 18 ]. Majority of the literatures reveal that PUFAs including linoleic acid, α-linolenic acid, γ-linolenic acid, were the major fatty acids in being extracted from mushroom biomass, with linoleic acid being the most abundant PUFA and this evidence suggested that linoleic acid plays a crucial role in mushroom metabolism, in which the level of fatty acid will be affected based on the growth conditions, substrate, and other environmental factors [ [16] , [17] , [18] , [20] , [21] , [22] , [23] , [24] ].…”
Section: Types Of Fatty Acids From Mushroom Biomassmentioning
confidence: 99%
“…It had been observed that oleic acid was the main fatty acid with the greatest percentage in the biomass of Russula anthracina (52.11 %) in the fatty acid composition analysis [ 18 ]. In addition to oleic acid, there were different MUFA being reported as the constituents of the fatty acid composition of mushroom species, such as, palmitoleic acid, eicosenoic acid, myristoleic acid, pentadecanoic acid, heptadecenoic acid, erucic acid, and nervonic acid, however, the level of these fatty acids are comparatively low to oleic acid level in the majority of the studied mushroom species [ [16] , [17] , [18] , [20] , [21] , [22] , [23] , [24] ].…”
Section: Types Of Fatty Acids From Mushroom Biomassmentioning
confidence: 99%
See 1 more Smart Citation